Thermal dissociation of anthracene photodimers in the condensed state: kinetic evaluation and complex phase behaviour. Issue 30 (20th July 2020) - Brancart, Joost; Van Damme, Jonas; Du Prez, Filip; Van Assche, Guy
Abstract : The kinetic parameters and the complex thermal dissociation behaviour of anthracene photodimers are reported above and below their melting temperatures. Abstract : Thermally and photochemically reversible functional groups, such as photodimers of anthracene derivatives, offer interesting stimuli-responsive behaviour. To evaluate their potential for application in reversible polymer networks, accurate kinetic parameters and knowledge of their thermophysical behaviour are required. Accurate kinetic studies of the thermal dissociation of the photodimers in the condensed state, thus without the influence of solvents on their reactivity, is still lacking. A methodology was set up to accurately evaluate the chemical reaction kinetics and complex phase behaviour during the thermal dissociation of photodimers into their corresponding monomers. Temperature-controlled time-resolved FTIR spectroscopy was used to determine the reaction progress, while non-isothermal DSC measurements were used to study the thermophysical changes, resulting from the thermal dissociation reaction. The thermal dissociation behaviour in the condensed state is more challenging than in the solution state due to the crystallinity of the dimers, stabilizing the dimers and thus slowing down the initial dissociation rates. Distinctly different sets of kinetic parameters were found for the dissociation from the molten and the crystalline state. For experiments performed below the melting temperature of the photodimer, the reaction rate changes abruptly as the dimer is partly dissociated and partly dissolved into the formed monomer. This methodology provides an accurate assessment of the reaction kinetics with detailed knowledge about the complex phase behaviour of the mixture of the anthracene photodimer and monomer during thermal dissociation.